Challenges and Opportunities in the Field of Business and Management - Oommen, Sherry Samuel (Ushus Journal of Business Management, 2021)
In this essay, the writer has placed his personal views regarding the subject and invites comments regarding the gravity of the situation. The writer seeks to highlight the point that in a capitalist economy, unless the forces of terror are destroyed, a nation cannot progress. The writer also speaks about the impending dangers of terror and the challenges it openly.